Sosialisasi Dan Pemanfaatan Sampah Organik Untuk Peningkatan Kreativitas Siswa Berkarya Seni Kelas IV SD - Titi Anjarini; Muflikhul Khaq; Rintis Rizkia Pangestika; Atikah Riswandani (Pakis Journal Institute, 2024)
Organic waste, one of which is leaves from various trees, is material that is not reused and has use value, as is the potential that exists in Kedungpoh Village, Loano District, Purworejo Regency, Central Java. Based on the results of observations made by the service team, there are several problems, namely 1) lack of student awareness of the importance of organic waste management, 2) lack of student understanding of how to sort organic waste. Therefore, the objectives of this service activity are 1) to raise student awareness about the importance of managing organic waste, 2) providing outreach and training in utilizing organic waste into creative work. This socialization and training activity consists of four stages, namely planning, implementation, implementation results, and evaluation stage. The method for this service is carried out by distributing questionnaires before and after socialization and training activities. The results of the questionnaire before training on question number 1 got an average score of 2. Questions numbers 2,3,4 and 5 got an average score of 2.1, thus showing that students' understanding, knowledge and experience in managing organic waste is still minimal. The results of the questionnaire after the training were that question number 1 got an average score of 3.7. Question number 2 got an average score of 3.8. Meanwhile, questions number 3,4 and 5 received an average score of 3.6, indicating that students' understanding and experience as well as students' creativity after socialization and training had increased significantly.